The Relationship between the Duration of Online Learning during the COVID-19 Pandemic and Symptoms of Depression in Medical Students of Pelita Harapan University: A Cross Sectional Study - Purnomo, Alexander Erick; Rivami, Dwi Savitri (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Introduction: The COVID-19 outbreak that started in Wuhan, China in December 2019 has become a global pandemic. The existence of the COVID-19 pandemic has led to a change in the university learning system into online learning. Online learning that occurs during the COVID-19 pandemic can have an indirect impact on the mental health of students, one of which is depression. Depression that occurs in online learning can be affected by the duration of online learning.Aim: This study is conducted to determine the relationship between online learning during the COVID-19 pandemic and symptoms of depression in medical students of Pelita Harapan University.Method: This study used a cross-sectional study to be conducted on 161 students of the Faculty of Medicine, University of Pelita Harapan. Sampling will use the purposive sampling method. Collecting data using a questionnaire about the duration of online learning and using the Patient Health Questionnaire-9 (PHQ-9) for depression symptoms. The results of this study were analyzed using chi-square analysis with data processing using SPSS 26.Results: There were 161 samples that matched the inclusion and exclusion criteria of this study. The majority of the sample was female (52.8%), came from the 2018 class (46.0%), 20 years old (50.3%), residing outside the Greater Jakarta area (57.8%), doing more online learning than 6 hours (57.8%) and experienced mild depression (53.4%). The results showed that there was no significant relationship between the duration of online learning and symptoms of depression (OR 1.273; 95%CI (0.669-2.421); p = 0.565).Conclusion: There was no significant relationship between the duration of online learning and symptoms of depression. Further studies with large samples and randomized sampling are required to minimize biases in future studies.